2011
DOI: 10.1136/bmj.d346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training traditional birth attendants on neonatal mortality (Lufwanyama Neonatal Survival Project): randomised controlled study

Abstract: Objective To determine whether training traditional birth attendants to manage several common perinatal conditions could reduce neonatal mortality in the setting of a resource poor country with limited access to healthcare. Design Prospective, cluster randomised and controlled effectiveness study. Setting Lufwanyama, an agrarian, poorly developed district located in the Copperbelt province, Zambia. All births carried out by study birth attendants occurred at mothers' homes, in rural village settings. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(202 citation statements)
references
References 23 publications
10
189
0
3
Order By: Relevance
“…65 In Zambia, we recently showed that training traditional birth attendants in newborn care with special emphasis on resuscitation and simple thermal protection (wiping the newborn dry and wrapping the dried infant in a separate piece of cloth) along with an intervention to provide early treatment of possible sepsis reduced mortality rates at day 28 after birth by 45%. 66 Low-cost, low-tech treatment of newborn hypothermia The use of incubators for thermal protection of newborns has been reported for more than 150 years, since the Parisian obstetrician Jean Louis Paul Denucรฉ in 1857 engineered his couveuse, a device Thermal protection of the newborn K Lunze and DH Hamer for the care of a premature infant. In 1878, his local colleague Stรฉphane Tarnier, using a modified warming chamber for the rearing of poultry, found a decrease in neonatal death rate from 66 to 38% among infants with birth weights <2000 g. 67 Today, postnatal care devices (isolettes or infant warmers) combine the features of incubators and radiant warmer beds and have evolved with many features, including automated temperature and humidity regulations, 68 oxygen supplementation and light therapy.…”
Section: Diagnosismentioning
confidence: 99%
“…65 In Zambia, we recently showed that training traditional birth attendants in newborn care with special emphasis on resuscitation and simple thermal protection (wiping the newborn dry and wrapping the dried infant in a separate piece of cloth) along with an intervention to provide early treatment of possible sepsis reduced mortality rates at day 28 after birth by 45%. 66 Low-cost, low-tech treatment of newborn hypothermia The use of incubators for thermal protection of newborns has been reported for more than 150 years, since the Parisian obstetrician Jean Louis Paul Denucรฉ in 1857 engineered his couveuse, a device Thermal protection of the newborn K Lunze and DH Hamer for the care of a premature infant. In 1878, his local colleague Stรฉphane Tarnier, using a modified warming chamber for the rearing of poultry, found a decrease in neonatal death rate from 66 to 38% among infants with birth weights <2000 g. 67 Today, postnatal care devices (isolettes or infant warmers) combine the features of incubators and radiant warmer beds and have evolved with many features, including automated temperature and humidity regulations, 68 oxygen supplementation and light therapy.…”
Section: Diagnosismentioning
confidence: 99%
“…More newborn deaths occur at home among the rural poor. Consistent with global trends almost 50% of all deliveries in Zambia take place at home or rely on traditional birth attendants as the nearest available source of maternity and delivery healthcare (4,7,9,10) . History has taught us that we do not need expensive technologies to facilitate the reductions of either maternal or newborn deaths (10) .…”
Section: Introductionmentioning
confidence: 84%
“…The role of community health workers in child survival is under debate as to the acceptability, level, function, type of incentives (12,13) . Traditional birth attendants and other CBAs continue to be the nearest source of care within the community (4,7,9,10,14,15,16,17,18,19) . This article describes cluster randomized community based trial in Zambia, with deliberate interventions in the pregnant mother.…”
Section: Introductionmentioning
confidence: 99%
“…This low rate compares favorably to chlorhexidine application trials conducted in south Asia (5% lost to follow-up in Bangladesh, and 2.5% lost to follow-up in Nepal) and newborn health trials in Africa. 7,8,22,23 Structural barriers. In Zambia, like many African countries, rural communities are widely dispersed, and families often travel great distances to reach primary health centers.…”
Section: Resultsmentioning
confidence: 99%